2020
DOI: 10.3390/cancers12040839
|View full text |Cite
|
Sign up to set email alerts
|

Effectiveness and Costs Associated to Adding Cetuximab or Bevacizumab to Chemotherapy as Initial Treatment in Metastatic Colorectal Cancer: Results from the Observational FABIO Project

Abstract: Evidence available on the effectiveness and costs of biological therapies for the initial treatment of metastatic colorectal cancer (mCRC) is scarce and contrasting. We conducted a population-based cohort investigation for assessing overall survival and costs associated with their use in a real-world setting. Healthcare utilization databases were used to select patients newly diagnosed with mCRC between 2010 and 2016. Those initially treated with biological therapy (bevacizumab or cetuximab) added to chemother… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
15
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(15 citation statements)
references
References 24 publications
(22 reference statements)
0
15
0
Order By: Relevance
“…The strength of this study was the RMST analysis. RMST was firstly proposed in 2010 and well established in Cardiovascular and Cancer studies as an alternative measure of the intervention effect [25,[39][40][41]. At present, most randomized controlled trials and observational studies in critical care evaluated the intervention effect with the increment or reduction of risk utilizing hazard ratio (HR) and its 95% CI [39].…”
Section: Discussionmentioning
confidence: 99%
“…The strength of this study was the RMST analysis. RMST was firstly proposed in 2010 and well established in Cardiovascular and Cancer studies as an alternative measure of the intervention effect [25,[39][40][41]. At present, most randomized controlled trials and observational studies in critical care evaluated the intervention effect with the increment or reduction of risk utilizing hazard ratio (HR) and its 95% CI [39].…”
Section: Discussionmentioning
confidence: 99%
“…Details of regional HCU databases of Italy and of the FABIO network have been previously reported. 9 Specific diagnostic and therapeutic codes used for this study are reported in Supplementary material ( Table S1 ).…”
Section: Methodsmentioning
confidence: 99%
“…Information on the number of patients still alive at each year of follow-up and the total number of deaths was used to solve the inverted KM equation, which allowed reconstruction of regional data for each arm, so obtaining pooled individual patients’ data. 9 , 12 Median survivals and restricted mean survival times (RMST) were reported as descriptive measures of survival in the two treatment arms. RMST, that is the area under the KM curve, represents the average survival time experienced by cohort members.…”
Section: Methodsmentioning
confidence: 99%
“…76 Several analyses have called into question the cost effectiveness of many new cancer drugs taking into account evidence of quality-lifeyears gained. 77,78 Despite these challenges, the expansion of ablation technologies and the potential for extension of survival in patients who traditionally would not qualify for surgery is an important and exciting prospect.…”
Section: Future Directionsmentioning
confidence: 99%
“…The addition of anti-PDL-1 (or PDL checkpoint inhibitors) prevents this negative feedback and maximizes the immunologic effect of cryoablation. Studies have shown that cryoablation potentiates dendritic cell efficacy, degree of T-cell induction and enhances anti-PDL blockade 78.…”
mentioning
confidence: 99%